2019
DOI: 10.3390/md17030171
|View full text |Cite
|
Sign up to set email alerts
|

Stereo-Selective Pharmacokinetics of Ilimaquinone Epimers Extracted from a Marine Sponge in Rats

Abstract: An ilimquinone (IQ) mixture isolated from Hippiospongia metachromia, consisting of IQ and epi-ilimaquinone (epi-IQ), exerts anti-HIV, anti-microbial, anti-inflammatory, and anti-cancer effects. An HPLC-MS/MS method was developed for simultaneous determination of the two epimers in rat plasma, separating them using a biphenyl column. Ascorbic acid is added during the sample preparation to ensure the stability of both isomers. The plasma concentrations of the isomers were monitored following intravenous and oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…The antimicrobial, anticancer, anti-inflammatory, and protein transport-inhibitory effects of IQ have been reported [ 14 , 16 , 27 , 28 ]. The pharmacokinetic features of IQ were also previously studied in rat models [ 29 , 30 ]. In a previous study, the GI 50 values of IQ on PC-3, DU145, LNCaP, MG63, A549, and Hep3B cells were found to be 2.6 to 19.8 μM at 48 h [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial, anticancer, anti-inflammatory, and protein transport-inhibitory effects of IQ have been reported [ 14 , 16 , 27 , 28 ]. The pharmacokinetic features of IQ were also previously studied in rat models [ 29 , 30 ]. In a previous study, the GI 50 values of IQ on PC-3, DU145, LNCaP, MG63, A549, and Hep3B cells were found to be 2.6 to 19.8 μM at 48 h [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The AUC for IQ was approximately six-fold higher than that of epi-IQ after i/v injection. After peroral administration, C max for IQ was 11.6-fold higher compared with epi-IQ, whereas the T max for both substances was almost the same ( Table 2 ) [ 46 ]. The absorption of ilimaquinone after the peroral administration of the mixture seems to be faster compared with single-compound administration [ 117 ].…”
Section: Pharmacokinetics Studies In Animalsmentioning
confidence: 99%
“…Although the T 1/2 values for both iso-forms were equal after mixture administration, the clearance of epi-IQ was much greater ( Table 2 ). The absolute bioavailability after peroral administration of the mixture was calculated as 38% and 13% for IQ and epi-IQ, respectively [ 46 ]. The results of this study highlight the importance of pharmacokinetic investigations of stereoisomers.…”
Section: Pharmacokinetics Studies In Animalsmentioning
confidence: 99%
“…With regard to pharmacokinetics, a recent study performed in rats reported an oral bioavailability of 45% after administration of 10 mg IQ /kg body weight (b.w.) [55]. The maximum plasma concentration determined for single oral administration was 0.94 µg/mL, which corresponds to approximately three µM.…”
Section: Discussionmentioning
confidence: 88%